Media ownership and control in Hong Kong, special administrative region (SAR) of the People's Republic of China : critical overview and assessment. - Tay, Jiun Kheng. (2008)
Media ownership in Hong Kong is being rapidly acquired by big corporate moguls who have only profit margin in mind and by pro-China business tycoons who are eyeing on the huge China market. The impact of this development on press freedom in Hong Kong calls for close attention. The focus of this dissertation is to research on the few corporate media owners in an effort to address economic and regulatory forces that influence media concentration, as well as strategies used by media organizations to adjust to a changing industry. The two keyresearch questions of this thesis are: (1) who are the key media players in Hong Kong? (2) How have economic and political forces influenced the media ownership patterns in Hong Kong? (2a): How do corporate media owners influence media coverage and the media industry?